Firm Structural Attributes and Capital Structure Adjustments among Listed Manufacturing Firms in Nigeria using Static and Dynamic Approaches - Ibrahim, Jimoh; Olalere Adebayo, Aderemi; Kolawole Olowookere, Johnson; Zaid Adeyemi , Adewumi; Moromoke Oladejo , Titilayo (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The study examined the effect of firm structural attributes on capital structure adjustments of Nigerian listed manufacturing companies. Out of the 56 listed firms 35 listed manufacturing firms were selected using the purposive sampling approach. Dynamic and static estimation techniques were applied. The results from both static and dynamic panel data revealed that assets tangibility had a positive and significant effect on capital structure adjustments with (t= 4.463; t = 2.965; p
Keywords: Assets Tangibility; Firm Size; Manufacturing Firms; Structural Attributes; Speed of Adjustments